The relationship between visual health and influencing factors among primary and secondary school students: a survey based in the Ningxia Hui Autonomous Region of China - Xu, Jiyan; Sang, Mengjiao; Xu, Weiwei; Feng, Kaijie (Frontiers in Medicine, 2024)
Introduction The myopia rate of young people around the world, especially in China, has continued to rise, and the vision health of primary and secondary school students has gradually become a global concern. It was to explore the current characteristics of vision status and their intrinsic links to influencing factors of the Ningxia Hui Autonomous Region primary and secondary school students under regional characteristics. Methods 1,670 primary and secondary school students in Ningxia Hui Autonomous Region were surveyed using Vision examination, International Physical Activity Scale, Lifestyle Behavior Scale. The data were analyzed using SPSS 25.0 and AMOS 23.0. Results The prevalence of myopia among primary and secondary school students in the Ningxia Hui Autonomous Region was 27.3%, with rates of 31.5% for girls and 23.4% for boys. There was a significant negative correlation between lifestyle behaviors (r = -0.36, p < 0.01) and physical activity level (r = –0.06, p < 0.05) with vision status. The physical activity level played a significant masking effect between lifestyle behaviors and vision status (a*b = 0.002, c’ = –0.044). Gender moderated the effects of lifestyle behaviors on physical activity level and vision status, as well as the effects of physical activity level on vision status. These factors constituted a mixed model with mediating and moderation. The model fitted well (RMSEA = 0.028, CFI = 0.951, NFI = 0.918). Discussion The prevalence of myopia among primary and secondary school students in this region is lower than the national average in China, and it is associated with lifestyle behaviors, physical activity level, and gender. When effectively controlled, the physical activity level significantly will reduce the prevalence of myopia as a masking variable. Gender, as a moderating variable, provides theoretical support for the classification and prevention of myopia. Regional surveys enriched the global database on adolescent myopia research, revealing the characteristics and common factors of visual problems in adolescents. Relevant departments and schools should integrate eye care into the national health security system, implement policies related to myopia prevention and control and safeguard the visual health of primary and secondary school students.